Distribution Of T.B. Among Women And Pediatric Age Group Attending T.B. Center In Kirkuk Province - Tahir, Suheila Shams-El-Den; Kadir, Mohammed Abdul-Aziz; Mawlood, Sharmin Mindan (Journal of the Faculty of Medicine Baghdad, 2007)
Bakground: A prospective study was designed to find out the prevalence of different types of T.B. among women and children.Methods: A total of 390 patients aged from less than one year up to more than 65 years who attended T.B. center in Kirkuk city from beginning to end of 2005, were included in the study. A detail clinical and laboratory examination were carried out to confirm the diagnosis.Results: The rate of infection in females (46.15%) was lower than males (53.84%). In pediatric age groups, the highest rate was among the age 12-14 (2.05%) and the lowest was among>1-2 years and 9-11 years (0.76%). Inactive pulmonary T.B. was highest among the pediatric age group.Conclusion: It is concluded that the rate of T.B. was high in both females and pediatric age group in Kirkuk province. Inactive T.B. was highest among pediatric age group from 12-14 years.